Curriculum outcomes, teaching practices and learner competencies in isiXhosa in three Grahamstown schools - Fobe, Mila Pamella (Rhodes University, Faculty of Humanities, School of Languages, 2014)
This study looks at the curriculum outcomes, teaching practices and learner competencies in isiXhosa at three Eastern Cape schools and across three different grades, 7-9. It explores the link between language learning and teaching as well as the teaching strategies used within the classroom. In particular, the study seeks to analyse how isiXhosa is taught at three different levels of instruction, namely at Home Language (HL), First Additional Language (FAL) and Second Additional Language (SAL) levels. Qualitative methods were used, and the study took the form of interpretive case studies within the respective schools. The purpose of using multiple case studies was to investigate the reality within the three sites selected. The three schools had three extreme settings, in the sense that one of the schools is a rich isiXhosa environment and the other two schools are English environments. The tools used for data gathering were interviews, classroom observations, and an analysis of documents from the Department of Basic Education. Data was then presented and analysed in Chapter 4 and 5 against the backdrop of an extensive literature review in Chapter 2 as well as a detailed methodological approach as outlined in Chapter 3. One of the findings of this research indicates that in two of the schools the teaching culture is largely from a western perspective, whereas in one of the schools the learners are primarily isiXhosa speaking and teachers use a different linguistic approach to imparting knowledge. In the private and ex-Model C school it was found that a lack of exposure to isiXhosa is the primary cause of language problems for L2 learners. Secondly the L1 is not appropriately maintained or promoted in the school environment because it is presumed that learners are sufficiently exposed to their L1 at home. The research found therefore that in this particular schooling environment there is an inconsistency between the curricula that is taught in relation to the linguistic abilities of the learners, many of whom are mother tongue speakers of isiXhosa. Furthermore and more generally, it was found that teachers are still not well informed concerning South Africa's Language-in-Education-Policy and there is a need for more inservice training that will focus on the nature of additional language acquisition in order to address the challenges of teaching these languages. The thesis concludes that extensive work needs to be done in order to reposition the teaching of isiXhosa at all three levels, but particularly at FAL level. This research shows that there is a disjuncture between the proposed curriculum/learning outcomes and the standards or levels achieved by the learners, more especially at FAL and SAL where oral proficiency in isiXhosa remains a challenge. Specific recommendations are contained in the final chapter of the thesis which also makes reference to the draft policy of the Ministry of Basic Education regarding the incremental introduction of the teaching of African languages from 2014 onwards. This thesis also makes takes as a point of departure the importance of multilingualism in a multicultural society such as South Africa where language is suggested as a strong factor in the fostering of social cohesion. It is for this reason that the thesis argues that the expert teaching of African languages, in this case isiXhosa, at both mother tongue and second language levels is of fundamental importance to the future of South African society.
Keywords: Xhosa language -- Study and teaching (Primary) -- South Africa -- Grahamstown; Xhosa language -- Study and teaching (Secondary) -- South Africa -- Grahamstown; Language and education -- South Africa -- Grahamstown; Curriculum planning; Second language acquisition; Public schools -- South Africa -- Grahamstown; Language policy -- South Africa